ESBL Escherichia coli Ventriculitis after Aneurysm Clipping: A Rare and Difficult Therapeutic Challenge - F. A. Zeiler; J. Silvaggio (Case Reports in Neurological Medicine)
Background. Extended spectrum beta-lactamase (ESBL) produced Escherichia coli (E. coli) ventriculitis is a rare infection of the central nervous system, with increasing rarity in the adult population. The therapeutic strategy to achieve cure may need to involve a combination of intraventricular and intravenous (IV) therapy. Objective. To describe a case of ESBL E. coli meningitis/ventriculitis in an adult and outline the antimicrobial therapy that leads to cure. Methods. We retrospectively reviewed the records of a patient admitted to the neurosurgical department for aneurysmal subarachnoid hemorrhage, who developed ESBL E. coli ventriculitis. Results. A 55-year-old female, admitted for a Fisher grade 3, World Federation of Neurological Surgeons grade 1, subarachnoid hemorrhage, developed ESBL E. coli ventriculitis requiring a combination of intraventricular gentamicin and high dose intravenous meropenem for clearance. Cerebrospinal fluid clearance occurred at 7 days after initiation of combined therapy. The patient remained shunt dependent. Conclusions. Meningitis and ventriculitis caused by ESBL E. coli species are rare and pose significant challenges to the treating physician. Early consideration for combined intraventricular and IV therapy should be made.